Emotional vocabulary and its functioning in story of Alexander Ivanovich Kuprin “Swamp” - S. Samedov, Jalil (2019)
The article is devoted to the problem of using words of different parts of speech in a work of fiction, which call emotions in direct meaning. The method of structural and semantic analysis identified and described the emotive lexemes contained in the story of A.I. Kuprina “Swamp”. The number of emotional units has been determined by facilities of the part of speech, as a result of which it was established that emotive adjectives (102 units) are the most common in the analyzed story. The contexts of the using of words are systematized, among which the most numerous were those where words with denotative seme “emotion” are combined with non-emotional lexemes. Attention is paid to the peculiarities of the individual author's use of complex emotive adjectives.  The theoretical significance of the results obtained is to identify the emotionally colored words in the story of A.I. Kuprin and their systematization by facilities of the part of speech; in clarifying of the meaning of the words of emotive semantics on the basis of their functioning in the language of a separate a work of fiction and in Russian language as a whole; in the description of contexts containing emotive vocabulary. The practical significance of the considered material is the possibility of applying of the results obtained in the practice of teaching the modern Russian language to a non-Russian audience and philological analysis of a literary text in scientific researches of this kind.